PHYTOCHEMICAL AND ANTIMICROBIAL ANALYSES OF LEAF EXTRACTS OF CERATHOTECA SESAMOIDES AND CHROMOLAENA ODORATA - M. A., Abubakar; Etonihu, A. C.; P. E., Kigbu; Owuna, J. E.; Audu, S. I. (International Journal of Research -GRANTHAALAYAH, 2020)
It was reported in 2005 during WHO survey that about 70-80% of the world population use medicinal plants either in their crude unmodified form or partially in their modified semi-synthetic form of plant sources in their primary healthcare. The present study investigated the phytochemicals and antimicrobial activities of the leaf extracts of Cerathoteca sesamoides and Chromolaena odorata to ascertain their potentials in herbal medicine. Fresh leaf of the plants obtained from Lafia in Nasarawa State, Nigeria were dried, powdered, and subjected to methanolic extraction, partition, phytochemical, and antimicrobial analyses using standard methods. Partitions from n-hexane, methanol, ethyl acetate, chloroform, and residue extracts were tested against clinical bacteria Escherichia coli, Klebsiella spp., Pseudomonas aeruginosa, Staphylococcus aureus, and fungus Candida albicans. Among the four different solvents used in partitioning methanolic and ethyl acetate extracts of both plants contain flavonoids, tannins, alkaloids, terpenoids, saponins, steroids, and cardiac glycosides. Saponins were absent in the n-hexane and chloroform extracts of C. odorata and the ethyl acetate extract of C. sesamoides. While flavonoids were present in the n-hexane extracts of C. odorata, they were absent in C. sesamoides. Anthraquinone and reducing sugar were absent in all the solvent extracts of both medicinal plants. The antimicrobial susceptibility tests showed that n-hexane and residue extracts of both plants had no activity against the tested microorganisms. The chloroform and ethyl acetate extracts of C. sesamoides and C. odorata (at 12.5 mg/ml) were active against all the tested clinical bacteria K. spp., E. coli, P. aeruginosa, S. aureus, and C. albicans. The methanolic extracts of both plants were active against the bacterial isolates but inactive against C. albicans. The minimum bactericidal concentration of these plant extracts was ≥50 mg, while the minimum inhibition concentrations ranged between 12.5 mg and ≥50 mg. The findings showed that the chloroform or ethyl acetate extracts of the leaves of these plant drugs could be used to treat urinary tract infections.